Lack of patients? - a hypothesis for understanding discrepancies between hospital resources and productivity - Bratlid Dag (BMC, 2006)
Abstract Background Despite a substantial increase in hospital resources, increased hospital admissions and out-patient visits, long waiting lists have been a significant problem in Norwegian health care. A detailed analysis of the development in resource allocation and productivity at St. Olavs University Hospital in central Norway was therefore undertaken. Methods Resource allocation and patient volume was analysed during the period 1995 to 2001. Data were analysed both for emergency and elective admissions as well as outpatient visits specified into new referrals and follow-up consultations. Results Full time employee equivalents for doctors and nurses increased by 36.6% and 25.9%, respectively, and all employees by 28.1%. However, admitted patients, outpatient consultations and surgical procedures only increased by 10%, 15% and 8.3%, respectively. Thus, the productivity for each hospital employee, defined as operations pr. surgeon, outpatient consultations pr. doctor etc. was significantly reduced. A striking finding was that although the number of outpatient consultations increased, the number of new referrals actually went down and the whole increase in activity at the outpatient clinics could be explained by a substantial increase in follow-up consultations. This trend was more evident in the surgical departments, where some departments actually showed a reduction in total outpatient consultations. Conclusion In view of the slow increase in hospital activity in spite of a significant increase in resources, it can be speculated that patient volume might be a limiting factor for hospital activity. The health market (patient population) might not be big enough in relation to the investments in increased production capacity (equipment and manpower).